Prinsip-Prinsip Ekonomi Syariah dalam Al-Qur’an: Telaah Sosial dalam Tafsir Al-Azhar - Sa'adah, Nismah; Dasuki , Akhmad; Ahmad , Balya Nasim (STAI Al Musaddadiyah Garut, 2024)
The growing severity of economic inequality caused by the dominance of global capitalism highlights the urgent need for an alternative economic system that is more just and socially oriented. In response to this condition, this study addresses the issue of how the principles of Islamic economics as outlined in the Qur'an can be interpreted to offer solutions to economic injustice. The aim of this research is to analyze the principles of Islamic economics through the social interpretation approach of Buya Hamka in his work Tafsir Al-Azhar. The method employed in this study is qualitative with a descriptive-analytical approach, using content analysis techniques on several Qur'anic verses, namely QS. Ar-Ra’d verse 11, QS. Al-A’raf verse 31, QS. Al-Isra’ verses 26–29, and QS. An-Nahl verse 90. The primary data are sourced from the text of Tafsir Al-Azhar, supported by literature review and empirical data on economic inequality in Indonesia. The results indicate that Buya Hamka interprets these verses contextually with a grounded approach, emphasizing the importance of hard work, moderation in consumption, responsible wealth management, and the application of justice and ihsan principles in wealth distribution. The conclusion of this study affirms that Buya Hamka’s interpretation of Islamic economic principles is highly relevant and offers practical solutions to contemporary economic challenges, particularly in building a fair, balanced, and welfare-oriented economic system. Keywords: Ekonomi Syariah, Tafsir Al-Azhar, Buya Hamka, Keadilan sosial;